1999
DOI: 10.3758/bf03207624
|View full text |Cite
|
Sign up to set email alerts
|

Haptic perception of linear extent

Abstract: The perception of linear extent in haptic touch appears to be anisotropic, in that haptically perceived extents can depend on the spatial orientation and location of the object and, thus, on the direction of exploratory motion. Experiments 1and 2 quantified how the haptic perception of linear extent depended on the type of motion (radial or tangential to the body) when subjects explored different stimulus objects (raised lines or solid blocks) varying in length and in relative spatial location. Relatively narr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
2
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 27 publications
4
32
2
5
Order By: Relevance
“…Size could be judged from the Euclidean distance between the spatial positions when touching the two extremities of the triangle. However, larger triangles may also be perceived as larger only because, on average, the stimulus had longer duration (22)(23)(24)(25)(26). We therefore analyzed reported sizes simultaneously as a function of simulated size and stimulus duration.…”
Section: Resultsmentioning
confidence: 99%
“…Size could be judged from the Euclidean distance between the spatial positions when touching the two extremities of the triangle. However, larger triangles may also be perceived as larger only because, on average, the stimulus had longer duration (22)(23)(24)(25)(26). We therefore analyzed reported sizes simultaneously as a function of simulated size and stimulus duration.…”
Section: Resultsmentioning
confidence: 99%
“…For example, observers who were instructed to trace linear extents at high speeds judged these lengths to be shorter than the same extents traced at considerably lower speeds (Hollins and Goble 1988;Von Skramlik 1933;Wapner et al 1967). In the case of free exploration, linear extents oriented radially from the body were judged to be longer than extents oriented tangentially; at the same time, it was observed that the extents that were judged longer were traced at slightly lower speeds, which led to a corresponding increase in movement time (Armstrong and Marks 1999;Wong 1977). Similarly, convex lengths were overestimated compared to concave lengths; again, these overestimations correlated with diVerences in movement time that were, in turn, due to slight speed diVerences between the various surface types (Sanders and Kappers 2008).…”
Section: Introductionmentioning
confidence: 98%
“…For example, curvature perception depends on whether the curvature is convex or concave (van der Horst & , the direction of movement over the surface (Davidson, 1972;Hunter, 1954), the position of the stimulus on the hand (Pont, Kappers, & Koenderink, 1997, 1998, and on shape features other than the judged curvature (Vogels, Kappers, & Koenderink, 1999). Haptic perception of linear extent is affected by the path length, curvature (Sanders & Kappers, 2008), rate of exploration between endpoints (Armstrong & Marks, 1999;Lederman, Klatzky, & Barber, 1985), and other linear elements in the field (Heller & Joyner, 1993).…”
Section: Manual Exploration For Haptic Perceptionmentioning
confidence: 99%